A novel hemicyanine-based near-infrared fluorescent probe for Hg2+ ions detection and its application in living cells imaging. (February 2020) - Wang, Yang; Hou, Xufeng; Li, Zhensheng; Liu, Chunhui; Hu, Shanshan; Li, Chenming; Xu, Zhihong; Wang, Yuan
Abstract: A novel hemicyanine-based near-infrared (NIR) fluorescence probe CY1OH2S for Hg 2+ ions detection was synthesized, which can selectively and sensitively responds to Hg 2+ ions based on the Hg 2+ -promoted deprotection of thioacetal. The probe exhibits good response and anti-interference performance for Hg 2+ ions based on the fluorescence enhancement in the NIR region under physiological conditions. The detection limit of probe CY1OH2S for Hg 2+ ions was as low as 0.32 μM. Probe-coated test paper was fabricated as a "naked-eye" indicator for Hg 2+ ions in water samples. In addition, probe CY1OH2S exhibited good cell permeability and was successfully applied in living cells by NIR fluorescence imaging. Graphical abstract: Image 1 Highlights: A novel hemicyanine-based NIR Hg 2+ fluorescent probe CY1OH2S  was designed and developed. CY1OH2S  can selectively detect Hg 2+  in vivo . The probe was designed based on a strategy by modulating the group nearby the hydroxyl group of the hemicyanine skeleton. CY1OH2S  was successfully applied to detect Hg 2+  on test strips and Hg 2+ in living HeLa cells.